Efektivitas Pendekatan Realistic Mathematic Education ditinjau dari Kemampuan Pemecahan Masalah Metematika Peserta Didik - Narmi Narmi; Nilam Permatasari; Edhy Rustan; Aswar Anas (Fakultas Tarbiyah dan Ilmu Keguruan, 2021)
Abstract[English]:This research aims to: 1) determine students' mathematics learning activities with the Realistic Mathematic Education (RME) approach; (2) knowing students' math problem solving using the RME approach; (3) determine the effectiveness of the RME approach in terms of mathematical problem solving abilities. This type of research is a quasi experiment. The design of this research is the One-Group Pretest-Posttest Design. The population and sample were students of class VII MTs. Batusitanduk, who were taken from one class of four classes, namely class VII A, totaling 39 people. The data collection instruments used were tests and observation sheets. The results showed that 1) students' learning activities were 90.13% in the very active category; 2) descriptively, the ability to solve mathematics problems increased from 21.49 in the low category to 77.18 in the high category; and 3) the results of the hypoethical test showed that there was a significant difference between students' mathematical problem solving abilities after applying the Realistic Mathematic Education (RME) learning approach.Abstrak[Indonesia]:Penelitian ini bertujuan untuk: 1) mengetahui aktivitas belajar matematika siswa dengan pendekatanRealistic Mathematic Education (RME); (2)mengetahui pemecahan masalah matematika siswa dengan menggunakanpendekatan RME; (3) mengetahui efektivitas pendekatan RME ditinjau dari kemampuan pemecahan masalah matematika. Jenis penelitian ini adalah quasi eksperimen. Desainpenelitian ini adalah One-Group Pretest-Posttest Design. Populasidan sampel adalah siswa kelas VII MTs.Batusitandukyang diambil satu kelas dari empat kelas yang ada, yaitu kelas VIIA yangberjumlah 39 orang. Instrumen pengumpulan data yang digunakan adalah tes dan lembar observasi. Hasil Penelitian menunjukkan bahwa 1) aktivitas belajar siswa sebesar 90,13% termasuk dalam kategori sangat aktif ; 2) secara deskriptif kemampuan pemecahan masalah matematika meningkat dari 21,49 berada pada kategori rendah, menjadi 77,18 berada pada kategori tinggi; dan 3) hasil uji hipoetsis menunjukkan terdapat perbedaan yang signifikan antara kemampuan pemecahan masalah matematika siswa setelah diterapkan pendekatan pembelajaran Realistic Mathematic Education (RME).